2019
DOI: 10.21203/rs.2.10716/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cloning and Functional Analysis of the FAD2 Gene Family from Desert Shrub Artemisia sphaerocephala

Abstract: Background: Linoleic acid is an important polyunsaturated fatty acid, required for all eukaryotes. Microsomal delta-12 (Δ12) oleate desaturase (FAD2) is a key enzyme for linoleic acid biosynthesis. Desert shrub Artemisia sphaerocephala is rich in linoleic acid, it has a large FAD2 gene family with twenty-six members. The objective of this work is to study the difference and potentially functionality of AsFAD2 family members. Results: Full-length cDNAs of twenty-one AsFAD2 genes were obtained from A. sphaerocep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The expression of LcFAD2 gene was highest in developing seeds. Similar expression profiles of FAD2 gene were also noticed in various other plants (Xue et al 2017;Miao et al 2019). The high expression level in seeds indicates that LcFAD2 gene is involved in linoleic acid accumulation during storage lipid biosynthesis as the similar expression was also shown in Idesia polycarpa and Olea europaea (Fan et al 2019;Herna ´ndez et al 2005).…”
Section: Discussionsupporting
confidence: 73%
“…The expression of LcFAD2 gene was highest in developing seeds. Similar expression profiles of FAD2 gene were also noticed in various other plants (Xue et al 2017;Miao et al 2019). The high expression level in seeds indicates that LcFAD2 gene is involved in linoleic acid accumulation during storage lipid biosynthesis as the similar expression was also shown in Idesia polycarpa and Olea europaea (Fan et al 2019;Herna ´ndez et al 2005).…”
Section: Discussionsupporting
confidence: 73%
“…Likewise, threes genes on chr2A (TaFAB2.1-3), chr2D (TaFAB2.9-11), chr5B (TaFAB 2. [26][27][28], and chr5A (TaFAB2. [23][24][25] are the result of tandem duplication.…”
Section: Gene Location On a Chromosome Gene Duplication And Selectimentioning
confidence: 99%
“…The FAD2 members have been shown to play important roles in wheat response to environmental stresses. Microsomal omega-six fatty acid desaturases (FAD2) introduce a double bond to the oleic acid (C18:1) carbon chain resulting in linoleic acid (C18:2) [28]. Linoleic acid is a precursor of other polyunsaturated fatty acids, and it is essential for the growth of all eukaryotes [29].…”
Section: Tafad26 and Tafad28 Structural Modeling And Docking Studiesmentioning
confidence: 99%
“…Likewise, threes genes on chr2A (TaFAB2.1-3), chr2D (TaFAB2.9-11), chr5B (TaFAB2. [26][27][28], and chr5A (TaFAB2. [23][24][25] are the result of tandem duplication.…”
Section: Gene Location On a Chromosome Gene Duplication And Selectimentioning
confidence: 99%
“…and TaFAD2.8 structural modeling and docking studies The FAD2 members have been shown to play important roles in wheat response to environmental stresses. Microsomal omega-six fatty acid desaturases (FAD2) introduce a double bond to the oleic acid (C18:1) carbon chain resulting in linoleic acid (C18:2)[28]. Linoleic acid is a precursor of other polyunsaturated fatty acids, and it is essential for the growth of all eukaryotes[29].…”
mentioning
confidence: 99%